Ease vs. noise: Long-run changes in the value of transport (dis)amenities - Gabriel M. Ahlfeldt; Volker Nitsch; Nicolai Wendland (Technische Universität Darmstadt, Department of Law and Economics, 2019)
For a complete cost-benefit analysis of durable infrastructures, it is important to understand how the value of non-market goods such as transit time and environmental quality changes as incomes rise in the long-run. We use difference-in-differences and spatial differencing to estimate the land price capitalization effects of metro rail in Berlin, Germany today and a century ago. Over this period, the negative implicit hedonic price of rail noise tripled. Our results imply income elasticities of the value of noise reduction and transport access of 2.2 and 1.4, substantially exceeding cross-sectional contingent valuation estimates.
urn:nbn:de:tuda-tuprints-91550
Keywords: R12; R14; R41; N73; N74; 330; Accessibility; spatial differencing; noise; difference-in-differences; income elasticity; land price